Nurse and allied health professional experiences and attitudes toward critical care research: A national questionnaire study. (February 2022) - Battle, Ceri; Lynch, Ceri; Discroll, Timothy; Thorpe, Chris; Hatchley, Bryony; Biggs, Sara; Phillips, Rebecca; Roberts, Alice; Roberts, Sian; Cole, Jade; Davies, Rhys; Hobrok, Maria; et al.
Introduction: The aim of this study was to investigate nurse and allied health professional experiences and attitudes toward critical care research in Wales. Methods: Data were collected related to demographic characteristics, involvement in and understanding of research, perceived influences and attitudes towards research. We calculated means (ranges) for continuous variable and frequencies (proportions) for discrete variables and performed an exploratory factor analysis. Results: Response rate was 55% ( n  = 575). Most respondents (84%) had participated in research less than five times in the previous 12 months, yet 91% believed research led to improved care patients. Only 32% respondents felt they were encouraged by managers to participate in research. Only 25% respondents had undertaken research training. Few respondents (29%) reported receiving adequate information regarding study progress or results (25%). Linear regression models indicate that a higher level of formal education was associated with a more positive view of research across all attitude factors. Promotion of research by colleagues and recognition/ opportunities for involvement in critical care research, were positively associated with the acceptability and experience of research. Discussion: A number of factors have been identified that could be targeted to improve recruitment to critical care research, including identification of staff to promote research, improved communication of study progress and findings and management encouragement to attend research training. Staff attitudes were positive towards the benefit of research on patient care in Wales.